Using Supply Chain Strategy in Skilled Workers Migration: A Consequence for the Russian Far East’s Economy - A. Andreev, Viacheslav; N. Arnaut, Marina; V. Varkulevich, Tat’ayna (International Journal of Supply Chain Management, 2019)
Supply chain management in human resource management of the workers in the large scale can be more efficient. Migration of highly skilled workers abroad and to the Russia’s central territories is becoming a significant problem for Primorsky region which located in the key geopolitical zone in the Russian Far East. Every year due to migration losses the population engaged in the economy squeezes by 0.3-0.4 percent. It determines a loss of public services’ quality in healthcare and education, and stipulates a degradation of business environment, which in turn limits the economic advances. Migration losses cause a change in demographic and ethnic structure of employment in the region, which in the long term will determine a structural imbalance in the labor force market. In addition, the outflow of labor force preconditions a slowdown of the economy and diminish the geopolitical status of the Russian Federation in the Far East due to depopulation process at the border’s areas. It can be managed by supply chain strategies to manage the forces properly in their own requirements. Migration of skilled workers, or